An overview of comparative modelling and resources dedicated to large‐scale modelling of genome sequences. Issue 8 (1st August 2017) - Lam, Su Datt; Das, Sayoni; Sillitoe, Ian; Orengo, Christine
Abstract : This paper reviews the recent advances in computational template‐based structural modelling and proposes the subclustering of protein domain superfamilies to guide the template‐selection process. Abstract : Computational modelling of proteins has been a major catalyst in structural biology. Bioinformatics groups have exploited the repositories of known structures to predict high‐quality structural models with high efficiency at low cost. This article provides an overview of comparative modelling, reviews recent developments and describes resources dedicated to large‐scale comparative modelling of genome sequences. The value of subclustering protein domain superfamilies to guide the template‐selection process is investigated. Some recent cases in which structural modelling has aided experimental work to determine very large macromolecular complexes are also cited.